Smoking cessation counseling practices in Jordan: Using the trans-theoretical model - Duaa M. Al-Hourani; Rawand A. Khasawneh; Samah F. Al‐Shatnawi; Eman Hammad; Salma Yasser Abu-Saleh (PLoS ONE, 2025)
The trans-theoretical model of behavior change (TTM) is widely used to assess an individual’s readiness to perform the new behavior and categorizes the behavior change into five stages: “pre-contemplation, contemplation, preparation, action, and maintenance.” This study focuses on assessing smoking cessation counseling practices (SCC) among Jordanian healthcare providers (HCPs) across various settings using the TTM. A cross-sectional study was conducted among HCPs (i.e., pharmacists, nurses, physicians, and dentists) working in private and public healthcare settings, using an online self-administered questionnaire. A total of 443 HCPs were included. One-third of HCPs reported asking patients if they smoked at their “first visit only.” Only 24.2% advised every patient to stop smoking, while 17.6% went beyond to assist smokers to make quit attempts, and (16.5%), assessed the willingness of the patients to quit and arrange follow-up quit attempts (10.6%). Only 28.4% of HCPs received training on SCC techniques. The majority of HCPs had a moderate level of confidence in performing SCC practices. HCPs in the private sector were more likely to be active in SCC practices than those in the public sector. Dentists and physicians were more involved in SCC practices than nurses and pharmacists. The study found a significant relationship between HCPs’ stage of change, self-efficacy, and performing SCC practices. This study affords a better understanding of the HCPs’ SCC practices. HCPs are found not to fully perform the “5 As” guidelines in their practices. Future efforts should focus on training and developing education programs that encourage HCPs to perform SCC practice.